The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2147/jmdh.s80337
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an educational intervention on provider knowledge, attitudes, and comfort level regarding counseling women ages 40–49 about breast cancer screening

Abstract: BackgroundMammography screening for women under the age of 50 is controversial. Groups such as the US Preventive Services Task Force recommend counseling women 40–49 years of age about mammography risks and benefits in order to incorporate the individual patient’s values in decisions regarding screening. We assessed the impact of a brief educational intervention on the knowledge and attitudes of clinicians regarding breast cancer screening.MethodsThe educational intervention included a review of the risks and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…After the program, the knowledge levels of the women about BC screening methods were reported to increase when compared with the scores prior to the training as in the present study, and it was found that their attitudes toward screening methods had taken a positive turn (18). Studies in Turkey have also reported that women's knowledge levels about BC increased after an educational program in a similar way to our research (7,18,19).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…After the program, the knowledge levels of the women about BC screening methods were reported to increase when compared with the scores prior to the training as in the present study, and it was found that their attitudes toward screening methods had taken a positive turn (18). Studies in Turkey have also reported that women's knowledge levels about BC increased after an educational program in a similar way to our research (7,18,19).…”
Section: Discussionsupporting
confidence: 86%
“…The present study showed that intervention via training was effective in increasing women's knowledge levels about BC (p=.001). Working with 40-to-49-year-old women in a study conducted in Alabama, Bryan et al (18) provided the women with an educational program designed to extend their information and change their attitudes about BC screening methods. After the program, the knowledge levels of the women about BC screening methods were reported to increase when compared with the scores prior to the training as in the present study, and it was found that their attitudes toward screening methods had taken a positive turn (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 37 Similarly, primary care physicians, key influencers in a woman’s screening decisions, are far less willing to refer patients 40–49 for screening when fully educated about the potential risks/benefits of screening. 38 …”
Section: What Women Want: Better Not More Screeningmentioning
confidence: 99%
“…Educational training programs were predominately delivered to staff working in residential care facilities and hospitals, and were aimed at physicians, nurse practitioners, nurses, and nursing assistants/aides. In the most recent years, only a handful of manuscripts were found that could be analyzed using Kirkpatrick's framework; these include the following trainees and topics: increasing physicians', nurse practitioners', and nurses' knowledge of the HPV vaccine (Berenson, Rahman, Hirth, Rupp, & Sarpong, 2015); increasing physicians' and nurses' knowledge and comfort levels regarding counseling about breast cancer screening (Bryan, Estrada, Castiglioni, & Snyder, 2015); increasing nurses' comfort level using tele-ultrasound (Douglas et al, 2019); increasing nurses' knowledge of and response to deteriorating patients (Liaw et al, 2016); determining knowledge and attitudes of nursing assistants about chronic pain in long-term care (Long, 2013); evaluating nurses' attitudes and beliefs about familycentered bedside rounds (Montgomery, Benzies, & Barnard, 2016); increasing nursing assistants' knowledge of challenging behaviors associated with dementia (Pfeifer, Vandenhouten, Purvis, & Zupanc, 2018); and improving the ability of nurses to recognize child abuse in the emergency department (Smeekens et al, 2011). A breakdown of the evaluation of these studies using Kirkpatrick's framework is provided below: Knowledge and Understanding (Berenson et al, 2015;Bryan et al, 2015;Douglas et al, 2019;Liaw et al, 2016;Long, 2013;Montgomery et al, 2016;Pfeifer et al, 2018) Attitudes and Beliefs (Bryan et al, 2015;Long, 2013;Montgomery et al, (Liaw et al, 2016;Pfeifer et al, 2018).…”
Section: Educational Interventions For Healthcare Personnelmentioning
confidence: 99%